Gamification Applications in Education, Health, Finance, and Marketing: A Bibliometric and Systematic Review - Meyjerd Rombebunga; Dedi Budiman Hakim; Popong Nurhayati; Nur Hasanah (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
Gamification, the use of game design elements in non-game contexts, has gained significant attention for enhancing motivation, engagement, and behavioral change across various fields. This study aims to examine the current state of gamification research, focusing on its applications, trends, and gaps in education, health, finance, and marketing. The research employs a quantitative approach, using the Preferred Reporting Items for Systematic Reviews and Meta-analyzes method and VOSviewer software to analyze 34 studies from the Scopus database, spanning 2015 to 2024. Gamification effectively boosts user engagement by incorporating elements like points, badges, and challenges in diverse domains. In education, it improves learning outcomes through interactive technologies. In health, it promotes adherence to wellness goals, while in finance, it encourages financial literacy. In marketing, gamification fosters eco-friendly behaviors and customer loyalty. The findings reveal a steady increase in publications, from 1,582 in 2015 to 11,949 in 2024, with key contributions from the United States and China. However, gaps remain in understanding long-term impacts and personalized strategies. This review concludes that gamification is a powerful tool for driving engagement, but further empirical research is needed to validate its long-term effectiveness and adaptability across diverse user groups. Keywords: gamification, prisma, systematic literature review